Psicoterapia racional emotiva - Amorós, Víctor (1990)
The following paper briefly describes the origin, basis, characteristics and technic of the emotional rational therapy of Albert Ellis. The author describes how persons create their own emotional and behavioural disturbs based on their wrong prejudgment and thoughts. He concludes asserting that irrational ideas in a special way origin neurosis. This work emphasizes the therapist's actitude that applies a directive technic reforcing the patient's cognitive components.